若lg(x-1)+lg(3-x)=lg(2-x),则x=
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 08:44:22
若lg(x-1)+lg(3-x)=lg(2-x),则x=若lg(x-1)+lg(3-x)=lg(2-x),则x=若lg(x-1)+lg(3-x)=lg(2-x),则x=lg(x-1)(3-x)=lg(
若lg(x-1)+lg(3-x)=lg(2-x),则x=
若lg(x-1)+lg(3-x)=lg(2-x),则x=
若lg(x-1)+lg(3-x)=lg(2-x),则x=
lg(x-1)(3-x)=lg(2-x)
(x-1)(3-x)=2-x
3x-3-x^2+x=2-x
x^2-x-x-3x+2=0
x^2-5x+2=0
x=(5±根号17)/2
x-1>0
x>1
所以x=(5+根号17)/2
-x²+4x-3=2-x
-x²+5x-5=0
x=无解
若lg(x-1)+lg(3-x)=lg(2-x),则x=
若lg,lg(2^x-1),lg(2^x+3),成等差数列,则x=?
lg(x-3)+lg(x-6)=1
求解方程lg(x+3)+lg(x-1)=lg(x^2-2x-3).
对数函数方程~lg(12-5x)-lg(3+2x)=lg(4-3x)-lg(2x+1)
lg^x+lg(x-3)=1的根前面是lg,x在上面 后面是lg(x-3)。
求解不等式lg(1-3x)=lg(3-x)=lg(7+x)
解方程lg(3-x)-lg(3+x)=lg(1-x)
若lg2,lg(2x-1),lg(2x-3)成等差数列,则x=?
不等式lg(x-3)+lg(x-2)
lg^x+6=lg²x
lg(2-x)-lg(x-1)>0
lg(2-2x)-lg(x+1)
lg(x^2-8x+9)=lg(3-x)
解方程lg(x²+x)=lg(x+1)
[2lg(x+1)+lg(-x+1)]/3可以化简吗
解方程:lg(x-1)+lg(x+2)=1
解方程lgx+lg(x-3)=lg(x+12)